Our Curricular Oath - Christou, Theodore; DeLuca, Christopher (Journal of the Canadian Association for Curriculum Studies, 2014)
What is curriculum? What unites curriculum theorists, disciplinary practitioners from wide-‐‑ranging subjects, constructs and practices? How might we be historically minded as we face the present and anticipate the past? Are discursive communities with diverse interests representing classroom practice, theory, teacher education, history, policy, and development, able to converse with each other? Are our conversations intelligible and open to the public at large? If they are not, why bother at all? We began to pose these questions in our last editorial. We continue to probe at them here. As the editors of JCACS, we are committed to characterizing the multivocal and interdisciplinary nature of the complicated conversation that is curriculum.